Isolation systems and its effectiveness in oral and maxillofacial surgery: A systematic review - Rahul V C. Tiwari; Anil Managutti; D Prasanna Lakshmi; Kunal Mohindru; Rajesh Damarasingu; Alok Dubey (Journal of Pharmacy and Bioallied Sciences, 2023)
Introduction: The success of restoration processes depends on the efficient control of moisture and microorganisms. Dental restorative procedures frequently use rubber dams as an isolation technique. There is still room for evidence-based discussion over how rubber dam use affects the durability and caliber of dental restorations. In this review, the effects of rubber dam isolation vs alternative isolation techniques for dental restorative procedures are compared. Materials and Procedures: An extensive online search in the various databanks of the EMBASE, Medline, Pubmed, and Scopus was conducted. The keywords searched were “isolation, oral surgery, dental surgery, retractors, rubber dam, and methods of isolation.” The studies selected were longitudinal research design and randomized trials. To ascertain the risk of bias, meta-analysis was carried out. The outcome was measured as the successful restoration at the end of follow-up period representing the thorough isolation. Results: A total of 1342 people were involved in six studies from across the world that were carried out between 2010 and 2015. High bias risk existed in all the studies. Five investigations compared the rubber dam vs cotton rolls. Due to discrepancies in the data supplied, one study was omitted from the analysis. Three of the four trials that were still running showed restored survival rates with all having a follow-up of at least six months. The survival of the restored composite teeth for six months in rubber dam isolation with odds ratio of 2.29, 1.38, and 1.00 at the end of six months, one year and one and half year respectively. However, the evidence was very low and speculative. The isolation was seen effective in the primary teeth specifically for the proximal lesions. None of the included studies discussed side effects or provided information on the treatment's upfront costs. Conclusion: The application of rubber dams in dental techniques may result in successful outcome compared to cotton rolls, according to some low-certainty evidence revealed in this research. Other times, the evidence is really ambiguous. It is necessary to conduct additional, high-quality studies investigating how rubber dam use affects various restorative procedures.